Mainstreaming Disability: Challenges and Strategies Toward Equality and Decent Work in Indonesia - Endah Tri Anomsari; Siti Widharetno Mursalim (Politeknik Negeri Bali, 2020)
This article aims to critically explore the challenges and strategies to mainstream disability in employment toward equality and decent work in Indonesia. Mainstreaming disability is important because Persons with Disabilities (PWDs) have a high risk to face extreme poverty and difficulties to get a chance for employment. Even if they are employed, they tend to earn less and experience discrimination. Using a qualitative approach, this critical analysis highlights the challenges including employment service accessibility, policy implementation, public facilities and mobility, and lack of awareness. While the strategies comprise of encouraging the law and policy changes, strengthening the government commitment, redesigning employment service, inclusive education provision, and awareness-raising. These strategies are expected to encourage inclusive and accessible by PWDs so that they can have decent work in the country.